Effective damping of the torsional vibrations of the drive system with an elastic joint based on the forced dynamic control algorithms. (August 2019) - Serkies, Piotr; Szabat, Krzysztof
The paper aims to present the novel control structures for a drive system with an elastic connection. Two control structures based on forced dynamic control (FDC) laws are investigated. The first one is based on the state controller approach, the second one on cascade methodology. These two approaches ensure different dynamic properties of the drive system. In the first approach, called full-FDC, the ability to remove the effect of the load torque from the load speed is assured, but the shaft torque cannot be directly limited. In the second approach the possibility of fast elimination of the load torque effect is limited, yet the shaft torque can be fully controlled. The detailed design methodology of both control structures is presented in the paper. Their properties are analyzed through simulation and experimental studies.